1997
DOI: 10.1021/jm9701031
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Nitric Oxide (NO) Deliveryin Vivo. Design of a Liver-Selective NO Donor Prodrug That Blocks Tumor Necrosis Factor-α-Induced Apoptosis and Toxicity in the Liver

Abstract: We have designed a drug that protects the liver from apoptotic cell death by organ-selective pharmacological generation of the bioregulatory agent, nitric oxide (NO). The discovery strategy involved three steps: identifying a diazeniumdiolate ion (R2N[N(O)NO]-, where R2N = pyrrolidinyl) that spontaneously decomposes to NO with a very short half-life (3 s) at physiological pH; converting this ion to a series of potential prodrug derivatives by covalent attachment of protecting groups that we postulated might be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
177
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 261 publications
(187 citation statements)
references
References 45 publications
9
177
0
1
Order By: Relevance
“…Expression of iNOS has also been shown to contribute to toxicity in models of alcohol-induced cirrhosis [23] and hepatitis induced by concanavalin A or acetaminophen. [22,29,30] These observations stand in contrast to studies in animal models of endotoxemia, [31,32] lipopolysaccharide/D-galactosamine (LPS/D-gal) administration, [33] hepatic regeneration [21] and cold ischemia/reperfusion following transplantation. [34] In each of these settings, either the absence or the inhibition of iNOS resulted in enhanced hepatocyte apoptosis.…”
Section: Nitric Oxide Synthesis and The Livermentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of iNOS has also been shown to contribute to toxicity in models of alcohol-induced cirrhosis [23] and hepatitis induced by concanavalin A or acetaminophen. [22,29,30] These observations stand in contrast to studies in animal models of endotoxemia, [31,32] lipopolysaccharide/D-galactosamine (LPS/D-gal) administration, [33] hepatic regeneration [21] and cold ischemia/reperfusion following transplantation. [34] In each of these settings, either the absence or the inhibition of iNOS resulted in enhanced hepatocyte apoptosis.…”
Section: Nitric Oxide Synthesis and The Livermentioning
confidence: 99%
“…Using a liver selective NO• donor, it was demonstrated that NO• almost completely inhibited the widespread cell death seen in this model. [33] Although the anti-apoptotic actions are profound, other iNOS-mediated protective effects include the inhibition of PMN influx [35] and improved liver perfusion. [36] The…”
Section: Nitric Oxide Synthesis and The Livermentioning
confidence: 99%
“…We and others have showed that administration with the agonistic anti-Fas antibody Jo2 and TNF-a þ GalN trigger fulminant hepatic failure by inducing in vivo caspase-dependent apoptosis. 22,23 We determined whether DEX prevents the apoptotic signaling pathway and liver injury in animal models. Intraperitoneal injection with DEX significantly increased cFLIP L -p43 expression in liver tissues compared with controls ( Figure 8a).…”
Section: Dex Also Suppresses Anti-fas Antibody-induced Hepatocyte Apomentioning
confidence: 99%
“…PABA/NO and several ester derivatives (9)(10)(11)(12)(13)(14) differing in the substitution pattern in the aroate ester functionality were synthesized in moderate to good yields from 7 or 8 (Table 1).…”
Section: Resultsmentioning
confidence: 99%